2021
DOI: 10.1021/acs.chemrev.1c00033
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning for Chemical Reactions

Abstract: Machine learning (ML) techniques applied to chemical reactions have a long history. The present contribution discusses applications ranging from small molecule reaction dynamics to computational platforms for reaction planning. ML-based techniques can be particularly relevant for problems involving both computation and experiments. For one, Bayesian inference is a powerful approach to develop models consistent with knowledge from experiments. Second, ML-based methods can also be used to handle problems that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
195
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 266 publications
(201 citation statements)
references
References 289 publications
0
195
0
6
Order By: Relevance
“…Generating full-dimensional, reactive PESs even for small molecules is a challenging task. 12,13 This often requires datasets consisting of tens of thousands of ab initio calculations to adequately describe configurational space of the system of interest. While calculations at the density functional theory (DFT) or Møller–Plesset perturbation (MP2) levels of theory are cost-efficient, reaction barriers are less accurate.…”
Section: Introductionmentioning
confidence: 99%
“…Generating full-dimensional, reactive PESs even for small molecules is a challenging task. 12,13 This often requires datasets consisting of tens of thousands of ab initio calculations to adequately describe configurational space of the system of interest. While calculations at the density functional theory (DFT) or Møller–Plesset perturbation (MP2) levels of theory are cost-efficient, reaction barriers are less accurate.…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning, which is a subset of ML, has been used in chemical reaction prediction [109] and to predict reaction yields [110] using interfaces like IBM RXN for Chemistry [111,112], which can be further modified to predict enzymatic reactions [113], and being open-source, these approaches can be readily modified to meet user requirements. Meuwly [114] reviewed the utility of ML methods for chemical reactions. To date, we are not aware of careful comprehensive comparisons of these methods which would suggest one approach is better than another, merely that applying such approaches culls CRNR outputs.…”
Section: Use Of Machine Learning (Ml) For Understanding Crnsmentioning
confidence: 99%
“…In this regard neural networks have shown promise in navigating the huge network space in organic molecular systems. Recently, a three layered neural network has been able to uncover retrosynthetic routes through the use of Monte Carlo tree search algorithms (Segler et al, 2018) based on reactions found in the Reaxys database, and we refer the reader to a recent review on machine-learning methods for more information (Meuwly, 2021). Compared to molecular synthesis, inorganic synthesis prediction is more complex, given the sheer number of elements, metastability and the possibility of new unchartered materials.…”
Section: Examples Of Topological Analysis Of Materials Networkmentioning
confidence: 99%